2012
DOI: 10.1038/nsmb.2439
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the variant histone H3.3–H4 heterodimer in complex with its chaperone DAXX

Abstract: Mammalian H3.3 is a variant of the canonical histone H3.1 essential for genome reprogramming in the fertilized eggs and maintenance of chromatin structure in neuronal cells. An H3.3-specific histone chaperone, DAXX, directs the deposition of H3.3 onto pericentric and telomeric heterochromatin. H3.3 differs from H3.1 by only five amino acids, yet DAXX can distinguish the two with high precision. By a combination of structural, biochemical and cell-based targeting analyses, here we show that Ala87 and Gly90 are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
118
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(130 citation statements)
references
References 29 publications
7
118
1
Order By: Relevance
“…In the chromatin-based transcription, the superhelical torsion locally disrupts DNA-histone contacts within the nucleosome (Sheinin et al 2013). In addition, the previous structural reports indicate competitive relationships between the nucleosomal DNA and several histone chaperones, including FACT, during the association with internal histones (Hu et al 2011;Winkler et al 2011;Elsässer et al 2012;Liu et al 2012;Chen et al 2015;Huang et al 2015;Kemble et al 2015;Richet et al 2015). Thus, we assumed that the interaction of hFACT with nucleosomes would involve local detachments of the nucleosomal DNA from histones (Winkler et al 2011;Hsieh et al 2013;Kemble et al 2015).…”
Section: Fact Binds To Dsb Nucleosomes In the Close Vicinity Of The Hmentioning
confidence: 99%
“…In the chromatin-based transcription, the superhelical torsion locally disrupts DNA-histone contacts within the nucleosome (Sheinin et al 2013). In addition, the previous structural reports indicate competitive relationships between the nucleosomal DNA and several histone chaperones, including FACT, during the association with internal histones (Hu et al 2011;Winkler et al 2011;Elsässer et al 2012;Liu et al 2012;Chen et al 2015;Huang et al 2015;Kemble et al 2015;Richet et al 2015). Thus, we assumed that the interaction of hFACT with nucleosomes would involve local detachments of the nucleosomal DNA from histones (Winkler et al 2011;Hsieh et al 2013;Kemble et al 2015).…”
Section: Fact Binds To Dsb Nucleosomes In the Close Vicinity Of The Hmentioning
confidence: 99%
“…In vivo , the assembly process is catalyzed by histone chaperones, a diverse class of proteins that is involved in histone turnover including transport, transfer, and storage (De Koning et al , 2007). Structural studies of histone chaperones bound to cognate histones have revealed that histone chaperones frequently protect hydrophobic histone interfaces that become solvent‐exposed outside of the context of the nucleosome or neutralize excess positive charge by providing an acidic binding pocket to directly compete with non‐specific electrostatic histone–DNA interactions (English et al , 2006; Zhou et al , 2008, 2011; Cho & Harrison, 2011; Hu et al , 2011; Elsasser et al , 2012; Liu et al , 2012; Hondele et al , 2013; Obri et al , 2014; Huang et al , 2015). However, how chaperones mediate the final deposition onto DNA to assemble nucleosomes remains poorly understood (Loyola & Almouzni, 2004; De Koning et al , 2007; Elsasser & D'Arcy, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…To monitor the interaction between CENP-A and CENP-N, we used a cell-based approach using the LacO/I targeting system in A03_1 cells (Supplemental Fig. S1A; Liu et al 2012). Initially, to test whether the LacI-CENP-A or LacI-H3 is incorporated into chromatin in our system, the retention ratio of LacI dots was analyzed following IPTG treatment.…”
Section: The Rg Loop Of Cenp-a Plays a Key Role In The Recruitment Ofmentioning
confidence: 99%
“…LacO/I targeting assays were performed as previously described with some modifications (Liu et al 2012). In brief, plasmids were transfected into cells with LipoD293 (SignaGen) according to the manufacturer's instructions.…”
Section: Laco/i Targeting Assaysmentioning
confidence: 99%